Benefits and Safety of Chinese Herbal Medicine in Treating Psoriasis: An Overview of Systematic Reviews - Jie Zhang; Jie Zhang; Qianying Yu; Li Peng; Li Peng; Yuesi Qin; Mingyi Jing; Mingyi Jing; Dan Huang; Dan Huang; Jing Guo; Min Xiao; et al. (Frontiers Media S.A., 2021)
Background: In recent years, systematic reviews/meta-analyses (SRs/MAs) of Chinese herbal medicine (CHM) for psoriasis have continuously emerged. Their methods and evidence quality, however, are yet to be evaluated, and whether their conclusions can provide clinicians with reliable evidence is still debatable.Objectives: This overview aims to evaluate the methodological quality, risk of bias, and reporting quality of relevant SRs/MAs, as well as the current evidence of CHM for treating psoriasis.Methods: We searched nine electronic databases from their respective time of establishment to January 20, 2021, as well as the reference lists of the included SRs/MAs, protocol registries, and gray literature. Two reviewers independently used the following: A Measurement Tool to Assess Systematic Reviews (AMSTAR) 2, Risk of Bias in Systematic Reviews (ROBIS), the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA), and Grades of Recommendations, Assessment, Development and Evaluation (GRADE) to evaluate the methodological quality, risk of bias, reporting quality, and evidence quality of the included SRs/MAs.Results: This review included 14 SRs/MAs involving 45 outcomes, of which 12 (85.71%) SRs/MAs had a very low quality evaluated by AMSTAR 2 and 7 (50.00%) SRs/MAs had a high risk of bias assessed by ROBIS. The protocol and registration and funding statements were the major reporting flaws according to the PRISMA checklist. The evaluation with the GRADE system demonstrated no outcome of high-quality evidence, and inconsistent efficacy evaluations were found in this overview. Only 15 (33.33%) outcomes were moderate-quality evidence, supporting the claim that CHM plus Western medicine (WM) was superior to WM. Generally low quality of evidence showed no difference in the incidence of adverse events between the combined therapy and WM. However, the conclusion that CHM was superior to WM cannot be drawn due to the inconsistent results.Conclusion: Despite that CHM has the potential benefit and safety in the adjuvant treatment of psoriasis, the conclusion should be treated with caution because of the generally low quality of methodology and evidence. In the future, high-quality randomized controlled trials (RCTs) should be carried out, and the quality of relevant SRs should also be improved to promote their clinical application.